Groundwater Pollution in Nanduru Region in Andhrapradesh - R. , Venkata Ramana; P. , Nageswara Rao (International Journal of Psychosocial Rehabilitation, 2020)
Groundwater is a fresh and renewable resource having more advantages than surface water. Groundwater is more important for the development of any region. Management of its quality becomes necessary due to its limited availability in many regions. Hence Hydrogeochemistry of groundwater is determined to understand its quality for domestic and agricultural use in an unconfined aquifer in the Nanduru region. Groundwater samples are collected and tested for determining the constituents present in them. Values of these constituents are greater than the prescribed limits. Water quality assessment parameters such as percent sodium, residual sodium carbonate, and sodium adsorption ratio are also determined. Values of these parameters indicate that this water is more polluted. The salt water intrusion, ion exchange reactions, evapotranspiration, and dissolution of carbonate minerals are the main processes responsible for regulating the chemistry of groundwater. As per the calculated parameters, high salinity and alkalinity of groundwater create problems for the cultivation of crops. This groundwater pollution leads to a decrease in soil quality and crop production. Proper management and maintenance of groundwater resources is advised to prevent its pollution and sustainability in this region.